2013
DOI: 10.5005/jp-journals-10024-1424
|View full text |Cite
|
Sign up to set email alerts
|

A Study to evaluate the Frequency and Association of Various Mucosal Conditions among Geriatric Patients

Abstract: In our study it was found that patients in groups II and III had more prevalence of oral mucosal disorders. Lingual varices, oral squamous cell carcinoma, fbroma and denture induced infammatory fbrous hyperplasia were more commonly associated with the geriatric patients. The oral lesions (fbroma and lichen planus) were strongly associated with women while leukoplakia was strongly associated with men. Ageing is an important factor that can infuence the occurrence of mucosal lesions and with age the oral mucosa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 25 publications
3
17
2
3
Order By: Relevance
“…[ 37 ] Lichen planus was observed in 1.6% of our study population, a finding similar to the ones reported by Reichart[ 24 ] and Shet et al . [ 13 ] The present authors observed lichen planus more frequently in women than in men. This finding has been confirmed by other authors.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…[ 37 ] Lichen planus was observed in 1.6% of our study population, a finding similar to the ones reported by Reichart[ 24 ] and Shet et al . [ 13 ] The present authors observed lichen planus more frequently in women than in men. This finding has been confirmed by other authors.…”
Section: Discussionsupporting
confidence: 48%
“…However, this rate is much higher than the results of other epidemiological studies, where investigators recorded a prevalence of 15.5–67%. [ 4 6 10 11 12 13 ] It is important to mention that it is difficult to compare results with those of other studies because of the methodological variability and sociocultural and demographic differences present in the studied populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reporting the incidence of oral lesions in older people have been published over the years . However, studies that exclusively evaluate the clinical diagnosis, although important, have the disadvantage of not reporting the accurate final diagnosis; for example, a clinical diagnosis of squamous cell carcinoma or of any other benign or malignant neoplasm can only be confirmed by biopsy and histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Only a slight diminution was observed in individuals who were more than 80 years old (10). However, in the presence of defined risk factors, such as smoking, premalignant and malignant changes in the oral mucosa may occur (64).…”
Section: Changes To the Oral Mucosa With Agingmentioning
confidence: 96%